The advertisement call of Haddadus binotatus (Spix, 1824) (Anura; Craugastoridae) - Moura, Mario Ribeiro; de Lacerda, João Victor Andrade; Feio, Renato Neves (Zootaxa, 2012)
We describe for first time the advertisement call of Haddadus binotatus Spix. This is a widely distributed species in Atlantic Forest of Brazil, occurring from the state of Bahia to the state of Rio Grande do Sul (Haddad et al. 2008), where it inhabits the leaf litter of the forest floor (Heyer et al. 1990). It is relatively common at the Serra do Brigadeiro mountain, a regional designation of the northeastern portion of the Serra da Mantiqueira mountain range, southeastern Brazil. In the Serra do Brigadeiro, the calling activity of H. binotatus comprehends all rainy season, from October to March (Feio et al. 2008). Although H. binotatus has been described almost two centuries ago, its vocalization is still unknown. The low volume of calls emitted by males, associated with the weather conditions in which they usually call (during the rain), turns difficult the detection of vocalizing individuals, which probably explains the absence of information on calling behavior in this species.